5y-26=-6(y+8)

Simple and best practice solution for 5y-26=-6(y+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y-26=-6(y+8) equation:


Simplifying
5y + -26 = -6(y + 8)

Reorder the terms:
-26 + 5y = -6(y + 8)

Reorder the terms:
-26 + 5y = -6(8 + y)
-26 + 5y = (8 * -6 + y * -6)
-26 + 5y = (-48 + -6y)

Solving
-26 + 5y = -48 + -6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6y' to each side of the equation.
-26 + 5y + 6y = -48 + -6y + 6y

Combine like terms: 5y + 6y = 11y
-26 + 11y = -48 + -6y + 6y

Combine like terms: -6y + 6y = 0
-26 + 11y = -48 + 0
-26 + 11y = -48

Add '26' to each side of the equation.
-26 + 26 + 11y = -48 + 26

Combine like terms: -26 + 26 = 0
0 + 11y = -48 + 26
11y = -48 + 26

Combine like terms: -48 + 26 = -22
11y = -22

Divide each side by '11'.
y = -2

Simplifying
y = -2

See similar equations:

| -2-10y+11y=-4 | | 17=-1-9a | | 4-0.7(p-3)=0.2(4p-3) | | 15+4x=5x+5 | | -9+x=.875x-23 | | -4x-4x=46-6 | | X^2+8x=2x^2+2x-40 | | X^12=9 | | yx+6x=7 | | 3/x^3-27 | | 12s-5-11s=-3+3 | | -9d-19=-11d+19 | | x^2+y^2-6x-16y+57=0 | | yx+6y=7 | | 300+20x=500+12y | | 16-0.3(m-13)=0.4(5m-13) | | r^2-20rs-44s^2=0 | | 4(2x-1)=-100 | | 3(1+4n)-3(5n-3)=25 | | 5-0.1(d-2)=0.5(5d-2) | | 3(x+1)-(3x+2)= | | -15(x-38)=x+(-44) | | (3x^2+4x)(15x^2-7x-4)=0 | | n=0.733(7)+8.398 | | 5-(4-1+2*1)= | | 4+1/3x=-5 | | 5-(4-0+2*0)= | | n=0.733(9)+8.398 | | 1.66666x=15 | | -9w+3-7+6w= | | 7/9x=21 | | 2x^2+18x-1944=0 |

Equations solver categories